2016
DOI: 10.1177/2050640615594939
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 serrated polyposis represents a predominantly female disease with a high prevalence of dysplastic serrated adenomas, without germline mutation in MUTYH, APC, and PTEN genes

Abstract: Aim: The aim of this article is to clarify the epidemiologic, clinical, endoscopic, biological and genetic characteristics of type 1 serrated polyposis patients. Patients and methods: Consecutive patients responding to the WHO definition of type 1 serrated polyposis in one reference center for polyposis patients accepted genetic counseling. Detailed data on previous endoscopies, histology, and life habits were recorded, after informed consent, germline analysis of MUTYH, APC, and PTEN germline mutations. Molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(92 reference statements)
0
4
1
Order By: Relevance
“…In our study from a single large tertiary referral center, gene panel testing identified pathogenic germline variants in 4% of those tested. This is higher than previously reported 33,34 . The two smaller previous studies found no pathogenic variants in the specific genes tested: PTEN, SMAD4, BMPR1A, MUTYH, GREM1, and APC.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…In our study from a single large tertiary referral center, gene panel testing identified pathogenic germline variants in 4% of those tested. This is higher than previously reported 33,34 . The two smaller previous studies found no pathogenic variants in the specific genes tested: PTEN, SMAD4, BMPR1A, MUTYH, GREM1, and APC.…”
Section: Discussioncontrasting
confidence: 65%
“…This is higher than previously reported. 33,34 The two smaller previous studies found no pathogenic variants in the specific genes tested: PTEN, SMAD4, BMPR1A, MUTYH, GREM1, and APC. In one study, 33 the majority (83.1%) of the patients fulfilled WHO 2010 criterion 3 (equivalent to WHO 2019 criterion 2), which differs from our cohort in which 85.5% (n = 148) fulfilled WHO 2019 criterion 1.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, these studies only examined limited risk factors including sex, smoking and CRC or polyp-affected first-degree relatives and were limited by study size and specific WHO criteria examined. The 2016 cohort study by Petronio et al found that people with WHO 2010 SPS criterion I were mostly women and there was a high prevalence of smokers, however, only 29 people were examined [ 17 ]. The large 2017 retrospective Dutch and British multicentre study involving 434 people with SPS found that only tobacco smoking had an inverse association with CRC in people with SPS, however, risk factors associated with SPS were not stratified by WHO criteria [ 16 ].…”
Section: Introductionmentioning
confidence: 99%